Implementation of Run Length Encoding (RLE) Algorithm on Text Data Compress using Python - Siradjuddin, Hairil Kurniadi; Khairan, Amal; Albaar, Muhammad Ridha; Abdullah, Saiful Do (Sistemasi: Jurnal Sistem Informasi, 2024)
Text data compression is done to make the file size smaller. Algorithm is a sequence of steps that aims to solve a problem. In this text data compress research using the Run Length Encoding (RLE) data compress method, it can be used to trim data to minimize the use of storage space so that it can be utilized better. As the function of the data compress itself to trim the file, its use is very beneficial for future technology. The programming applied is a python application, applying the concept of structured programming. Structured programming is a programming concept or paradigm that solves problems structurally, without looking at objects or divisions but must be structured, The result of this research is that the phyton application is able to trim text data so as to minimize the use of storage space so that it can be utilized better.